1986
DOI: 10.1177/0887302x8600400206
|View full text |Cite
|
Sign up to set email alerts
|

Salience of Disability Cues in Functional Clothing: A Multidimensional Approach

Abstract: This paper provides data on perceptions of functional clothing, augmenting a theoretical framework integrating symbolicinteractionist and cognitive approaches. A self-administered questionnaire was completed by 322 physically disabled university students throughout the nation. One half of the students evaluated line drawings of only one view of each clothing style, whereas the other half rated illustrations presenting an additional view detailing the special, functional feature of the garment. The students res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…For example, clothing might need to be modified to allow access to IV ports or catheters necessitated by impairments in body function, or might interfere with the ability to use assistive devices and thus a person's ability to execute different activities (Banks 2001;Garner and Douglas 1991;Nessley and King 1980;Wang et al 2014;White and Dallas 1977). Further, clothing can increase feelings of stigma that influence the desire or ability to engage in social participation (Carroll and Gross 2010;Carroll and Kincade 2007;Freeman, Kaiser, and Wingate 1985;Wingate, Kaiser, and Freeman 1986). For many PLWD, "…dressing in patient clothing can be a metaphor for illness or other health problems" (Topo andIltanen-Tähkävuori 2010, 1685).…”
Section: Disability Assessment and Impacts On Social Participationmentioning
confidence: 99%
“…For example, clothing might need to be modified to allow access to IV ports or catheters necessitated by impairments in body function, or might interfere with the ability to use assistive devices and thus a person's ability to execute different activities (Banks 2001;Garner and Douglas 1991;Nessley and King 1980;Wang et al 2014;White and Dallas 1977). Further, clothing can increase feelings of stigma that influence the desire or ability to engage in social participation (Carroll and Gross 2010;Carroll and Kincade 2007;Freeman, Kaiser, and Wingate 1985;Wingate, Kaiser, and Freeman 1986). For many PLWD, "…dressing in patient clothing can be a metaphor for illness or other health problems" (Topo andIltanen-Tähkävuori 2010, 1685).…”
Section: Disability Assessment and Impacts On Social Participationmentioning
confidence: 99%
“…Wingate, Kaiser, and Freeman (1986) also reported a difference in clothing choice between those with congenital and acquired disabilities. They found that those with acquired disabilities were more likely to choose functional clothing that is normative in appearance than those with congenital disabilities.…”
Section: Demographic Variables and Perceived Riskmentioning
confidence: 99%
“…For example, O'Bannon, et al (1988) sampled consumers in Missouri who used wheelchairs. Miller (1980) sampled individuals with physical disabilities from the Lansing, Michigan area, while Wingate, Kaiser, and Freeman (1986) sampled students with disabilities from 72 colleges and universities across the country. Miller (1980) sampled individuals with physical disabilities from the Lansing, Michigan area, while Wingate, Kaiser, and Freeman (1986) sampled students with disabilities from 72 colleges and universities across the country.…”
Section: Previous Samplesmentioning
confidence: 99%
“…It was based in part on a questionnaire developed by Wingate, Kaiser, and Freeman (1986). The highest response rate was achieved using the third approach.…”
Section: Sample Selectionmentioning
confidence: 99%